Perbedaan Zona Hambat Terhadap Jamur Malassezia Furfur Antara Pemberian Ekstrak Umbi Bawang Putih (Allium Sativum Linn) Dengan Ekstrak Kulit Umbi Bawang Putih (Allium Sativum Linn) - Diah Ariana (Universitas Muhammadiyah Surabaya, 2018)
Tinea versicolor or pitiriasis versicolor is a skin disorder caused by Malassezia furfur infection which is a fungal infection on the skin of the chronic surface. Clinical features is in the form of fine spots that colored white to brown black, this infection is also called a skin fungus with blotches. Treatment of Tinea versicolor can use chemical or traditional medicine. Chemical treatments such as creams or ointments cause sticky taste, while one of the traditional medicine is the bulb and skin of the garlic bulb (Allium sativum Linn) containing allicin substances that are efficacious as an anti-fungal. This research is an experimental research with the aim to know the difference of inhibition zone to Malessezia furfur fungus. There are 3 treatments with 9 repetitions. The extraction method used is the soxhlet method. Anti-fungal activity test was done by using rating method, Saboroud Dextrose Agar (SDA) media which has been inoculated with suspension of Malassezia furfur with concentration 1.5x108 CFU/ml (Mc Farland standard). Result of data analysis obtained by ANOVA p = 0,000 < α = 0,05, that there is difference of inhibition zone from treatment of garlic bulb extract and skin of garlic bulb (Allium sativum Linn). It is indicated that there is effect of giving garlic bulb extract (Allium sativum Linn) and garlic bulb skin (Allium sativum Linn) to Malassezia furfur fungus. Further tests were performed to compare mean treatment i.e. HSD test. It was obtained sig (p) 0,016 > α 0,05 which means bulb extract and garlic bulb skin (Allium sativum Linn) have different effect. Keywords: Tinea versicolor, Malassezia furfur, garlic bulb.